Gestos e atitutes em medicina centrada no doente num serviço de medicina interna. - Carneiro, Rui; Freire, Elga; Alves, Júlia; Rocha, Nelson (Acta Médica Portuguesa, 2010)
We made a cross-sectional study aimed at 50 professionals (18 doctors, 32 nurses) of a tertiary hospital Internal Medicine (IM) ward, focusing the relevant knowledge in various areas of Patient-Centered Care in Chronic Disease: symptom control, pharmacology and palliative prognostic discussion. Almost 98% believe that most patients need strategies for symptomatic care, which died in hospital in considerable suffering (68%). Provision of palliative care in the community was rarely established with the primary health team. 90% were favourable on the creation of a hospital palliative care team. Around 57% find essential to prognosticate before thinking about mitigation strategies. While 75% of professionals had already discussed end-of-life directives with, at least, one patient, only one case could be formalized in writing. The rate of use of scales for assessing the intensity of pain was less than 50% and 38% did not indicate major opioids for the treatment of moderate intensity pain. These were considered contra-indicated for relief of dyspnoea in chronic obstructive pulmonary disease by 20% of professionals and 55% of those were unaware that its use and titration is governed by the same principles used in pain control. Around 44% of the respondents had already used the subcutaneous route for administration of drugs and 58% for hydration. Despite the team recognition of the potential for suffering of patients and the need for mitigation strategies, they remain linked to prognosis and not to symptomatic complexity. There are gaps in regard to control of pain, dyspnoea and in continuity of care.